1978
DOI: 10.1136/gut.19.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tumour ferritins in primary liver cancer.

Abstract: SUMMARY Serum ferritin concentrations were found to be raised, often considerably, in 58 of 76 black patients with primary liver cancer (PLC). No correlation could be demonstrated between the serum ferritin concentration and several other measurements, including the following: hepatic iron stores measured chemically, the size of the tumour, serum transaminase values, and the presence or absence of cirrhosis in the non-tumorous liver. There was, however, a negative correlation between serum ferritin and alpha-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 15 publications
3
26
1
Order By: Relevance
“…In a study of serum and tumor ferritins in HCC in Black Africans, the nontumorous liver tissue of 6 of 17 patients contained chemical iron in the range expected in patients with advanced hereditary hemochromatosis, and heavy iron deposits were evident in the hepatocytes on histological examination. 20 A recent proportional mortality analysis of the 1920s autopsy series, in which Strachan first described iron overload in Africans, showed an association between high hepatic iron levels and death from HCC. 21 Because of the limited information obtained in this study concerning the presence of coexisting cirrhosis, we are unable to state whether iron loading is an independent cause of the tumor or acts as an indirect carcinogen by inducing chronic necroinflammatory hepatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of serum and tumor ferritins in HCC in Black Africans, the nontumorous liver tissue of 6 of 17 patients contained chemical iron in the range expected in patients with advanced hereditary hemochromatosis, and heavy iron deposits were evident in the hepatocytes on histological examination. 20 A recent proportional mortality analysis of the 1920s autopsy series, in which Strachan first described iron overload in Africans, showed an association between high hepatic iron levels and death from HCC. 21 Because of the limited information obtained in this study concerning the presence of coexisting cirrhosis, we are unable to state whether iron loading is an independent cause of the tumor or acts as an indirect carcinogen by inducing chronic necroinflammatory hepatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of various solid tumours, including tumours of the breast, pancreas and liver an increase of H-subunit rich ferritins was shown in the cells of the tumour, as well as an increase in plasma ferritin. In addition, the plasma ferritins reflected the increase in H-subunit rich ferritins of the tumour, therefore the tumours seem to produce and secrete these H-subunit rich ferritins (Kew et al, 1978;Niitsu et al, 1984).…”
Section: Extracellular Ferritinmentioning
confidence: 99%
“…Ferritin has been known as an iron storage protein and used for diagnosing iron deficiency anemia and iron overload. On the other hand, it was regarded as a tumor associated antigen (Marcus et al, 1979) A high serum ferritin level in lung cancer (Gropp et al, 1978), leukemia (Jones et al, 1973), primary hepatoma (Kew et al, 1978), and other malignant diseases (Niitsu et al, 1975) has been reported.…”
Section: Discussionmentioning
confidence: 99%